Enucleolation and nucleolus transfer in mammalian oocytes and zygotes - Benc, Michal; Fulka, Josef Jr; Strejček, František; Morovič, Martin; Murín, Matej; Martínková, Stanislava; Jettmarová, Dominika; Laurinčík, Jozef (The International journal of developmental biology, 2019)
The oocyte GV/GVs (germinal vesicle/germinal vesicles) and zygot PN/PNs (pronucleus/pronuclei) of some mammals contain clearly visible nucleoli which exhibit an atypical morphological structure. These nucleoli (NCLs) can be relatively easily manipulated, i.e. removed from GVs/PNs or eventually transferred into another oocyte/zygote. Thus, with the help of micromanipulation techniques it was possible to uncover the real function(s) they play in processes of oocyte maturation and early embryonic development. The purpose of our review is to describe briefly the micromanipulation techniques that can be used for oocyte/zygote nucleoli manipulation. Moreover, we present some examples of results that were obtained in nucleolus manipulation experiments.
Keywords: Mice; oocyty; zygota; Swine; Animals; Micromanipulation; partenogeneze; Zygote; mikromanipulace; Oocytes; Cell Nucleolus; zvířata; myši; prasata; Parthenogenesis; buněčné jadérko